2012
DOI: 10.1590/s0102-05362012000200012
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation effect on in vitro organogenesis, callus growth and plantlet development of Gerbera jamesonii

Abstract: The present work was carried out to study the effects of gamma irradiation on in vitro growth of explants, callus and the formation of shoots and plantlets. Irradiation is known to exhibit or inhibit the differentiation of cells and growth of plants in vitro, which helps in producing new plant varieties. Gamma irradiation is one of the physical mutagens that are widely used for mutation breeding. A gradual decline was observed in the number of shoots regenerated from irradiated petiole explants compared to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
2
21
0
5
Order By: Relevance
“…Contrast to these findings of Domingo et al [17] reported reduction in height of M 2 Oryza sativa cv Bahia (japonica) mutagenised with FN. Also, Hasbullah et al [21] suggested that irradiation may prohibit the auxin activities and change the morphogenetic responses in plant.…”
Section: Plant Heightmentioning
confidence: 99%
“…Contrast to these findings of Domingo et al [17] reported reduction in height of M 2 Oryza sativa cv Bahia (japonica) mutagenised with FN. Also, Hasbullah et al [21] suggested that irradiation may prohibit the auxin activities and change the morphogenetic responses in plant.…”
Section: Plant Heightmentioning
confidence: 99%
“…Kondisi ini dapat diketahui dari pertambahan bobot kalus pada setiap minggu tidak begitu terlihat perubahannya (Gambar 1A). Pertambahan bobot basah kalus yang sangat kecil akibat dari perlakuan iradiasi pada dosis yang relatif tinggi juga terjadi pada kalus tanaman Gerbera jamesonii (Hasbullah, 2012).…”
Section: Pengaruh Iradiasi Sinar Gama Terhadap Pertumbuhan Kalusunclassified
“…Kandungan air pada kalus cukup tinggi sehingga kemampuan iradiasi sinar gama dalam menghambat dan mematikan kalus berhubungan dengan kandungan air dalam kalus yang tinggi. Selain itu, iradiasi sinar gama juga dapat menurunkan biosintesis hormon endogen pada kalus yang dapat menghambat pertumbuhan kalus (Hasbullah, 2012).…”
Section: Pengaruh Iradiasi Sinar Gama Terhadap Pertumbuhan Kalusunclassified
See 1 more Smart Citation
“…Berbagai penelitian telah menghasilkan perubahan kualitatif pada tanaman hasil iradiasi diantaranya dilaporkan oleh Hasbullah et al (2012) bahwa iradiasi sinar gamma mempengaruhi perubahan warna kalus pada tanaman hias Gerbera jamesonii dari putih menjadi coklat tua dan perubahan warna daun dari hijau tua menjadi hijau muda. Singh dan Anjana (2015) menghasilkan mutan gladiol warna kuning muda pada generasi MV3.…”
Section: Bahan Dan Metodeunclassified